2011
DOI: 10.1007/s00268-011-1393-z
|View full text |Cite
|
Sign up to set email alerts
|

Fungating Thyroid Cancer: A Complex Clinical Scenario

Abstract: Eleven patients were referred with fTC, eight of whom had undergone subtotal thyroidectomy for an undiagnosed well-differentiated thyroid cancer (DTC) in another institution. The final pathological diagnosis showed (DTC, n = 3), poorly differentiated thyroid cancer (n = 5), anaplastic cancer (n = 2), and medullary thyroid cancer (n = 1). Extensive resections and reconstruction using flaps (pectoralis major, n = 6; deltopectoral, n = 1; sternocleidomastoid, n = 1) were undertaken. Complete tumor clearance (R0) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Nabawi AS et al has reported 11 cases with thyroid malignancy with cutaneous fungating lesion in which the final diagnosis showed DTC=3, poorly differentiated thyroid carcinoma=5, anaplastic cancer=2, medullary thyroid cancer=5. 5 Our case report is a papillary thyroid carcinoma presented as maggot infested fungating extrathyroidal mass, and similar case has not been reported before in the English literature. Preoperative evaluation in our case required management of myiasis by local application of turpentine oil and antibiotic coverage for one week.…”
Section: Discussionsupporting
confidence: 77%
“…Nabawi AS et al has reported 11 cases with thyroid malignancy with cutaneous fungating lesion in which the final diagnosis showed DTC=3, poorly differentiated thyroid carcinoma=5, anaplastic cancer=2, medullary thyroid cancer=5. 5 Our case report is a papillary thyroid carcinoma presented as maggot infested fungating extrathyroidal mass, and similar case has not been reported before in the English literature. Preoperative evaluation in our case required management of myiasis by local application of turpentine oil and antibiotic coverage for one week.…”
Section: Discussionsupporting
confidence: 77%
“…This would reflect on the strictness and duration of patient follow‐up and would highlight possibilities of future disease recurrence. This is especially important in Egypt with limited follow‐up facilities due to the rural nature, resulting in patients being lost to follow‐up and re‐presenting several years later with very aggressive disease, as previously reported by our group [22]. In the present study we compared changes in serum leptin levels in patients with WDTC before and after surgery and in control subjects.…”
Section: Discussionmentioning
confidence: 84%